Development of a four-tier gamified diagnostic test to identify students' misconceptions in Ejaan Yang Disempurnakan (Eyd) V - Moh. Faridl Darmawan Faridl; Faisol Hidayatulloh Faisol; Afif Kholisun Nashoih (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aimed to develop an evaluation instrument based on the Four-Tier Gamified Diagnostic Test (FT-GDT) to identify studentsâ€™ misconceptions regarding the General Guidelines for Indonesian Spelling (PUEBI). The instrument consisted of 25 multiple-choice items with five answer options for the first and third tiers, and two confidence options (â€œconfidentâ€ and â€œnot confidentâ€) for the second and fourth tiers, producing 100 items in total. The development employed a Research and Development (R&D) approach adapted from Borg and Gall. Expert validation indicated high feasibility, with average scores of 86.7% from subject matter experts and 88.3% from media experts. Empirical validity testing showed that most items met the required criteria (r â‰¥ 0.254), while reliability testing with 40 students produced a Cronbachâ€™s Alpha of 0.87, indicating strong internal consistency. Misconception analysis revealed that studentsâ€™ misconceptions ranged from 17.5% to 45%, with many students expressing high confidence in incorrect answers. These findings demonstrate that the misconceptions were conceptual rather than merely technical errors. Overall, the FT-GDT instrument proved effective in identifying misconceptions in PUEBI learning, highlighting its potential as a diagnostic and formative evaluation tool in higher education.